2000
DOI: 10.1037/0278-7393.26.1.204
|View full text |Cite
|
Sign up to set email alerts
|

Metacognitive and control strategies in study-time allocation.

Abstract: The issue of how people use their metacognitive judgments about what they know and how well they know it to take control over their own learning is of primary concern in this article. The fact that in many situations people have relatively accurate metacognitions is well documented (Brown, 1978;, 1997 Gnmeberg & Monks, 1974; Jacoby, Bjork, & Kelley, 1993;Johnson, 1988;Johnson & Raye, 1981;King, Zechmeister, & Shaughnessy, 1980;Koriat, 1975Koriat, , 1993Koriat, , 1995Koriat, , 1997Koriat, , 1998Koriat & Goldsm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
322
3
3

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 326 publications
(357 citation statements)
references
References 84 publications
(133 reference statements)
19
322
3
3
Order By: Relevance
“…The fact that self-controlled learning was suboptimal may have been a result of the instructions participants were given, which emphasized mastery of all items (see Metcalfe, 2002). More recent findings suggest that people select in a manner that is very much in keeping with Atkinson's theory, if not his data (Metcalfe, 2000;Metcalfe & Kornell, 2005). Like Atkinson, Mazzoni and Cornoldi (1993, Experiment 3) found that self-controlled study was more effective than random study-time allocation.…”
Section: Previous Findings On the Effectiveness Of Metacognitivelymentioning
confidence: 97%
“…The fact that self-controlled learning was suboptimal may have been a result of the instructions participants were given, which emphasized mastery of all items (see Metcalfe, 2002). More recent findings suggest that people select in a manner that is very much in keeping with Atkinson's theory, if not his data (Metcalfe, 2000;Metcalfe & Kornell, 2005). Like Atkinson, Mazzoni and Cornoldi (1993, Experiment 3) found that self-controlled study was more effective than random study-time allocation.…”
Section: Previous Findings On the Effectiveness Of Metacognitivelymentioning
confidence: 97%
“…This was done in Experiment 6, which capitalized on the finding that under time pressure learners spend more time studying the easier items (Metcalfe, 2002;Son & Metcalfe, 2000). We argue that time pressure produces a qualitative change in study time allocation from being data driven to being goal driven because learners must, in fact, operate against the data-driven tendency to invest more study time in the more difficult items.…”
Section: Introduction To the Experimentsmentioning
confidence: 95%
“…In other studies, however, students have selected material for restudy which they believed to be relatively easy (i.e., information that was retrievable), probably because they want to rehearse this material (e.g., Metcalfe & Kornell, 2003;Thiede & Dunlosky, 1999;Son & Metcalfe, 2000) and this seemed much more beneficial than dropping material from further study (Karpicke & Roediger, 2007).…”
Section: Performance On Initial Tests As a Mediator For Restudy Behaviormentioning
confidence: 99%